2023
DOI: 10.1186/s13044-023-00150-y
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer metastases in thyroid: case report and literature review

Abstract: Background The thyroid gland is an uncommon site for metastatic deposits from non-thyroid malignancies, occurring in only 1.4 - 3% of surgical specimens where malignancy is suspected. It is even rarer for the source of thyroid metastases to be of colorectal origin. In most cases reported, colorectal metastases in the thyroid occurs many years later after the primary colorectal cancer has been diagnosed and treated. In this unique case, a primary sigmoid carcinoma metastasised to the thyroid gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…After all, the diagnostic accuracy seems to be affected by the type of malignancy. Metastatic adenocarcinomas of breast, lung, and colorectal origin are often correctly diagnosed, whereas metastatic squamous cell carcinomas of oesophageal and cervical origin can be challenging to diagnose [6]. FNA accurately diagnosed colorectal cancer thyroid metastases in our case.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…After all, the diagnostic accuracy seems to be affected by the type of malignancy. Metastatic adenocarcinomas of breast, lung, and colorectal origin are often correctly diagnosed, whereas metastatic squamous cell carcinomas of oesophageal and cervical origin can be challenging to diagnose [6]. FNA accurately diagnosed colorectal cancer thyroid metastases in our case.…”
Section: Discussionmentioning
confidence: 69%
“…A literature review of metachronous colon metastases to the thyroid gland by Froylich et al identified only 34 cases from 1931 to 2013 originating from the following sites: rectum (41%), sigmoid colon (33%), ascending colon (19%), and descending colon (11%) [9]; since the review in 2013, Hussein et al reported 14 cases describing thyroid metastases of colorectal origin [6]. What is more, in a comprehensive systematic review by Manatakis et al, 111 patients were identified to have colorectal thyroid metastasis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, metastatic malignant tumors of the thyroid are relatively rare ( 8 ), accounting for only 1.4–3.0% of all malignant thyroid tumors ( 9 , 10 ). However, the proportion of metastatic malignant tumors found in autopsy results is as high as 9.5% ( 11 ).…”
Section: Discussionmentioning
confidence: 99%